Functional activity within the frontal eye fields, posterior parietal cortex, and cerebellar vermis significantly correlates to symmetrical vergence peak velocity: an ROI-based, fMRI study of vergence training - Alvarez, Tara L.; Jaswal, Raj; Gohel, Suril; Biswal, Bharat B. (Frontiers in Integrative Neuroscience, 2014)
Convergence insufficiency (CI) is a prevalent binocular vision disorder with symptoms that include double/blurred vision, eyestrain, and headaches when engaged in reading or other near work. Randomized clinical trials support that Office-Based Vergence and Accommodative Therapy with home reinforcement leads to a sustained reduction in patient symptoms. However, the underlying neurophysiological basis for treatment is unknown. Functional activity and vergence eye movements were quantified from seven binocularly normal controls (BNC) and four CI patients before and after 18 hours of vergence training. An fMRI conventional block design of sustained fixation versus vergence eye movements stimulated activity in the frontal eye fields (FEF), the posterior parietal cortex (PPC) and the cerebellar vermis (CV). Comparing the CI patients’ baseline measurements to the post vergence training data sets with a paired t-test revealed the following: 1) the percent change in the BOLD signal in the FEF, PPC and CV significantly increased (p<0.02), 2) the peak velocity from 4° symmetrical convergence step responses increased (p<0.01) and 3) patient symptoms assessed using the CI Symptom Survey (CISS) improved (p<0.05). CI patient measurements after vergence training were more similar to levels observed within BNC. A regression analysis revealed the peak velocity from BNC and CI subjects before and after vergence training was significantly correlated to the percent BOLD signal change within the FEF, PPC and CV (r=0.6;p<0.05). Results have clinical implications for understanding the behavioral and neurophysiological changes after vergence training in patients with CI, which may lead to the sustained reduction in visual symptoms.